Answer:
The exponential funtion is "height(n) = 77*(0.9925)^n". After 15 years he is 68.7778 inches.
Step-by-step explanation:
Since Tom's initial height is 77 inches. After one year:
height(1) = 77*(1 - 0.0075) = 77*0.9925
After two years:
height(2) = height(1)*(0.9925) = 77*0.9925*(0.9925) = 77*(0.9925)²
After three years:
height(3) = height(2)*0.9925 = 77*(0.9925)²*0.9925 = 77*(0.9925)³
And so on, therefore the expression that represents his height is:
height(n) = 77*(0.9925)^n
Where n is the number of elapsed years. For 15 years we have:
height(15) = 77*(0.9925)^(15) = 68.7778 inches
The exponential funtion is "height(n) = 77*(0.9925)^n". After 15 years he is 68.7778 inches.